Improving Pupils' Conscience of Learning English Language Through Culture (Program Studi Pendidikan Bahasa Inggris, FKIP - Universitas Iskandar Muda, 2023)
Instead of being isolated, they are less successful now since they do not speak a second language. Spanish is where the proverb